2021
DOI: 10.1177/0192513x211048479
|View full text |Cite
|
Sign up to set email alerts
|

Mothers’ Well-Being in Families and Family Structure: Examining Constellations of Stressors Across Life Domains

Abstract: Identifying conditions under which parents thrive is a key concern of family research. Prior research often focused on mothers’ well-being in single life domains, yet it is more likely to be shaped by stressors that stem directly from the parenting role and related stressors emerging from spillover processes into other domains. We therefore examine how stressors concerning mothers’ subjective, relational, and financial well-being accumulate and combine within subgroups of mothers and whether the likelihood to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Differences in maternal well-being between lone and partnered mothers have been documented by a large body of research before the pandemic (e.g., Avison et al, 2007;Cairney et al, 2003;Dziak et al, 2010;Kühn, 2018;Recksiedler et al, 2023). These disparities arise in part because of pre-existing differences in the distribution of resources and stressors by family structure and could have widened during the pandemic.…”
Section: Maternal Well-being and Family Structure Before And During T...mentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in maternal well-being between lone and partnered mothers have been documented by a large body of research before the pandemic (e.g., Avison et al, 2007;Cairney et al, 2003;Dziak et al, 2010;Kühn, 2018;Recksiedler et al, 2023). These disparities arise in part because of pre-existing differences in the distribution of resources and stressors by family structure and could have widened during the pandemic.…”
Section: Maternal Well-being and Family Structure Before And During T...mentioning
confidence: 99%
“…In turn, mothers reported higher ratings of psychological distress and parental stress, as well as lower ratings of life satisfaction, compared to fathers during the COVID-19 pandemic (e.g., Dib et al, 2020;Li et al, 2021;Möhring et al, 2021). Mixed findings emerged on the pandemic's impact on lone mothers (e.g., Hiekel & Kühn, 2022;Mata et al, 2021;Thomeer, 2023), who were already at a higher risk of suffering from poor mental health before the pandemic because of their exposure to multiple chronic stressors (e.g., higher poverty risk, increased time pressure to manage work and family duties; Chzhen & Bradshaw, 2012;Recksiedler et al, 2023;Pollmann-Schult, 2018;Wickrama et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Lone mothers have become a more heterogeneous group in terms of age, education, and socioeconomic status over the last decades (Bernardi et al, 2018). Yet being a lone mother is still a strong predictor of poverty and financial strain, fragmented work histories, lower life satisfaction, and poorer health due to the exposure to chronic stressors in multiple life domains (Brady & Burroway, 2012;Bull & Mittelmark, 2009;Pollmann-Schult, 2018;Recksiedler et al, 2021). Furthermore, employed lone mothers tend to experience more time pressure and higher levels of family-to-work conflict (Kendig & Bianchi, 2008;Nieuwenhuis & Maldonado, 2018;Reimann et al, 2020).…”
Section: The Role Of Family Structurementioning
confidence: 99%
“…To address the research gap on linkages between work-to-family conflict and parenting practices by family structure, we ask whether the direction and magnitude of these associations vary between lone and partnered mothers. This may occur because lone mothers tend to have fewer psychological, social, and economic resources than partnered mothers to cope with the demands from multiple life domains on their own (W. Bakker & Karsten, 2013;Dziak et al, 2010;Recksiedler et al, 2021). Likewise, when lone mothers have to cope with high work demands, their limited amount of resources may also hinder their capacity for supportive parenting more strongly.…”
Section: The Role Of Family Structurementioning
confidence: 99%
“…While LPA has frequently and effectively been used in studying patterns of risk and adversity, it has been less often applied to the study of more general family function. Previous research utilizing person-centered methodologies in family well-being have consistently found a latent subgroup of individuals who are doing well despite stress exposure, including maternal well-being prior to COVID-19 ( Recksiedler et al, 2021 ), Chinese adolescents with largely improving family and social relationship during COVID-19 ( Shen et al, 2021 ), and international families (with and without children) brought together despite COVID-19 social distancing regulations ( Chavez et al, 2021 ). While these studies have found a range of functioning profiles across myriad indicators, their findings suggest that thriving is consistently evident in the wake of adversity.…”
Section: Introductionmentioning
confidence: 99%